High-dimensional phenotyping of the peripheral immune response in community-acquired pneumonia - Reijnders, Tom D. Y.; Schuurman, Alex R.; Verhoeff, Jan; van den Braber, Marlous; Douma, Renée A.; Faber, Daniël R.; Paul, Alberta G. A.; Wiersinga, W. Joost; Saris, Anno; Garcia Vallejo, Juan J.; van der Poll, Tom (Frontiers in Immunology, 2023)
Background Community-acquired pneumonia (CAP) represents a major health burden worldwide. Dysregulation of the immune response plays an important role in adverse outcomes in patients with CAP. Methods We analyzed peripheral blood mononuclear cells by 36-color spectral flow cytometry in adult patients hospitalized for CAP (n=40), matched control subjects (n=31), and patients hospitalized for COVID-19 (n=35). Results We identified 86 immune cell metaclusters, 19 of which (22.1%) were differentially abundant in patients with CAP versus matched controls. The most notable differences involved classical monocyte metaclusters, which were more abundant in CAP and displayed phenotypic alterations reminiscent of immunosuppression, increased susceptibility to apoptosis, and enhanced expression of chemokine receptors. Expression profiles on classical monocytes, driven by CCR7 and CXCR5, divided patients with CAP into two clusters with a distinct inflammatory response and disease course. The peripheral immune response in patients with CAP was highly similar to that in patients with COVID-19, but increased CCR7 expression on classical monocytes was only present in CAP. Conclusion CAP is associated with profound cellular changes in blood that mainly relate to classical monocytes and largely overlap with the immune response detected in COVID-19.